The Charlson Comorbidity and Barthel Index predict length of hospital stay, mortality, cardiovascular mortality and rehospitalization in unselected older patients admitted to the emergency department - Bahrmann, Anke; Benner, Laura; Christ, Michael; Bertsch, Thomas; Sieber, Cornel; Katus, Hugo; Bahrmann, Philipp (Aging clinical and experimental research, 2018)
Background and aims: The Charlson Comorbidity Index (CCI) is the most widely used assessment tool to report the presence of comorbid conditions. The Barthel index (BI) is used to measure performance in activities of daily living. We prospectively investigated the performance of CCI or BI to predict length of hospital stay (LOS), mortality, cardiovascular (CV) mortality and rehospitalization in unselected older patients on admission to the emergency department (ED). We also studied the association of CCI or BI with costs.Methods: We consecutively enrolled 307 non-surgical patients ≥ 68 years presenting to the ED with a wide range of comorbid conditions. Baseline characteristic, clinical presentation, laboratory data, echocardiographic parameters and hospital costs were compared among patients. All patients were followed up for mortality, CV mortality and rehospitalization within the following 12 months. A multivariate analysis was performed. Results: Mortality was increased for patients having a higher CCI or BI with a hazard ratio around 1.17-1.26 or 0.75-0.81 (obtained for different models) for one or ten point increase in CCI or BI, respectively. The prognostic impact of a high CCI or BI on CV mortality and rehospitalization was also significant. In a multiple linear regression using the same independent variables, CCI and BI were identified as a predictor of LOS in days. Multiple linear regression analysis did not confirm an association between CCI and costs, but for BI after adjusting for multiple factors.ConclusionCCI and BI independently predict LOS, mortality, CV mortality, and rehospitalization in unselected older patients admitted to ED.